2021
DOI: 10.1183/20734735.0112-2021
|View full text |Cite
|
Sign up to set email alerts
|

Progress in precision medicine in cystic fibrosis: a focus on CFTR modulator therapy

Abstract: The genetic multisystem condition cystic fibrosis (CF) has seen a paradigm shift in therapeutic approaches within the past decade. Since the first clinical descriptions in the 1930s, treatment advances had focused on the downstream consequences of a dysfunctional cystic fibrosis transmembrane conductance regulator (CFTR) chloride ion channel. The discovery of the gene that codes for CFTR and an understanding of the way in which different genetic mutations lead to disruption of normal CFTR function have led to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 60 publications
0
8
0
4
Order By: Relevance
“…Regarding CFTR modulators, IVA (a first‐generation modulator) is known as a potentiator that binds to defective CFTR on the cell surface, keeping the chloride gate opened; LUM and TEZ (first‐generation modulators) as well as ELX (next‐generation modulator), are known as correctors that bind to different sites on defective CFTR proteins, increasing the number of mature CFTR proteins on the cell surface. 7 , 8 Some studies have tested the combination of LUM/IVA and reported rescue of CFTR function with positive results in patients with a homozygous c.1521_1523delCTT mutation.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding CFTR modulators, IVA (a first‐generation modulator) is known as a potentiator that binds to defective CFTR on the cell surface, keeping the chloride gate opened; LUM and TEZ (first‐generation modulators) as well as ELX (next‐generation modulator), are known as correctors that bind to different sites on defective CFTR proteins, increasing the number of mature CFTR proteins on the cell surface. 7 , 8 Some studies have tested the combination of LUM/IVA and reported rescue of CFTR function with positive results in patients with a homozygous c.1521_1523delCTT mutation.…”
Section: Discussionmentioning
confidence: 99%
“…It has been deduced that individuals homozygous for mutations I-III tend to have less functional CFTR protein, leading to worse phenotypes. On the other hand, patients with class IV-VI mutations frequently have a milder phenotype [ 4 ].…”
Section: Reviewmentioning
confidence: 99%
“…Given that declining lung function and pulmonary exacerbations are the leading causes of death in CF patients, all trials documented patient improvement based on these parameters. Furthermore, because pulmonary function tests are easily measurable and quantifiable, they have become the primary outcome of interest in clinical trials [ 4 ]. Elexacaftor/tezacaftor/ivacaftor improved forced expiratory volume in one second (FEV1) by 14 points in Phe508del heterozygotes at 24 weeks compared to placebo and by 10 points in homozygotes at four weeks, over tezacaftor/ivacaftor.…”
Section: Reviewmentioning
confidence: 99%
See 2 more Smart Citations